Pengaruh Trust Dan Communication Terhadap Customer Retention Pada Adikuasa Photography Di Taman Cari Purbolinggo Lampung Timur - Refiana, Eva; Japlani, Ardiansyah (Universitas Muhammadiyah Metro, 2021)
Each company certainly has its own strategy in attracting customers and keeping customers from moving to competing companies. The problem in Adikuasa Photography is that the number of subscribers tends to decrease. The research design is quantitative research or verification research. The method used in this research is explanatory survey method. The objects in this study are trust, communication and customer retention. The study population and sample were 93 respondents. The data collection technique used a questionnaire. The analytical tool used is to use data quality analysis and multiple linear regression analysis with the SPSS program. The results showed that partial trust and communication have a significant effect on customer retention. Simultaneously it also shows that trust and communication together have a significant effect on customer retention. Based on the number of coefficients and the value of tcount, it can be seen that the factors that most influence on customer retention is communication.